1993
DOI: 10.1080/00306525.1993.9632660
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Demographical Variation in Intestinal Helminth Infection of Greywing Francolin

Abstract: Ostrich ISSN: 0030-6525 (Print) 1727-947X (Online) Journal homepage: http://www.tandfonline.com/loi/tost20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Davidson et al (1977) reported that juvenile ruffed grouse (Bonasa umbellus) in the United States had higher intensities of infection than adults, whereas Moore et al (1987) showed that there was no significant difference between age or sex regarding intensities of infection in bobwhite quail. Little et al (1993) also found no significant difference between age and sex classes in the prevalence of helminth infection in greywing francolin. This study conforms with Crowe (1977) in that first-year guineafowl had higher intensities of infection than adults but, unlike Crowe's (1977) findings, female guineafowl in this study had significantly higher intensities of infection than males.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Davidson et al (1977) reported that juvenile ruffed grouse (Bonasa umbellus) in the United States had higher intensities of infection than adults, whereas Moore et al (1987) showed that there was no significant difference between age or sex regarding intensities of infection in bobwhite quail. Little et al (1993) also found no significant difference between age and sex classes in the prevalence of helminth infection in greywing francolin. This study conforms with Crowe (1977) in that first-year guineafowl had higher intensities of infection than adults but, unlike Crowe's (1977) findings, female guineafowl in this study had significantly higher intensities of infection than males.…”
Section: Discussionmentioning
confidence: 65%
“…Saayman (1966) also found low incidence of insects in guineafowl diet during winter. Additionally, Little et al (1993) showed that cestode infection in greywing francolin (Scleroptila africanus) was lowest in winter and also attributed this to their seasonally variable diet.…”
Section: Discussionmentioning
confidence: 99%